Slamming : the Unauthorized Change of a Consumer's Telephone Service Provider. (U.S. Congressional Research., 2001)
Examines Federal Communications Commission policies to protect consumers from unauthorized switching of their long distance carriers (slamming), including new rules under the Telecommunications Act of 1996, and reviews General Accounting Office reports and 105th-106th Congress activity and legislation relating to slamming. Discusses industry initiatives and issues raised by legislative and other efforts to curb slamming.